Roman and medieval coins found in Scotland, 2001-2005 - Bateson, J D; Holmes, N M McQ (Proceedings of the Society of Antiquaries of Scotland, 2007)
Coins and other numismatic finds from some 270 locations across Scotland are listed and discussed.